Biosafety of Adenoviral Vectors - Chuah, Marinee K.L.; Collen, Desire; VandenDriessche, Thierry (Current Gene Therapy, 2003)
Adenoviral vectors can efficiently transduce a broad variety of different cell types and have been used extensively in preclinical and clinical studies. However, early generation of adenoviral vectors retained residual adenoviral genes that contribute to inflammatory immune responses and toxicity. In addition, these vectors often result in transient expression of the potentially therapeutic transgene. Some clinical trials based on early generation adenoviral vectors have been discontinued because of acute inflammatory responses and toxicity and even one patient has died as a direct consequence of adenoviral toxicity. The latest generation of highcapacity adenoviral vectors is devoid of viral genes, and is having a significantly improved safety profile and yielding more prolonged transgene expression compared to early generation vectors. Nevertheless, transgene expression gradually declines even when high-capacity adenoviral vectors are used, possibly due to the gradual loss of vector genomes. Despite their improved safety, high-capacity adenoviral vectors can still trigger transient toxic effects in animals and patients. Restricting the tropism of adenoviral vectors by immunologic or genetic retargeting may further improve their therapeutic window. The safety of adenoviral vectors has been improved further through the development of safer packaging systems that eliminate the homologous overlap between vector and helper sequences and therefore prevent formation of replication-competent adenoviruses (RCA). RCA could exacerbate inflammatory responses and act as a helper to rescue adenoviral vectors, potentially increasing the effective vector dose. Conditionally replicating adenoviruses (CRAds) have been developed for cancer gene therapy, which replicate selectively in some cancer cells. The use of CRAds in combination with chemotherapy yielded therapeutic effects in patients suffering from cancer but dose-limiting toxicity was apparent. Although there appears to be a very low theoretical risk of malignancy that is predominately associated with the occurrence of E1-positive recombinants, no malignancies have been reported that were associated with adenoviral vectors. Nevertheless, integrating adenoviral vectors carry a greater malignancy risk due to their ability to integrate randomly into the target genomes.
Keywords: replication-competent adenoviruses (RCA)